Response of the fine root morphological and chemical traits of Tamarix chinensis to water and salt changes in coastal wetlands of the Yellow River Delta - Sun, Jia; Xia, Jiangbao; Shao, Pengshuai; Ma, Jinzhao; Gao, Fanglei; Lang, Ying; Xing, Xianshuang; Dong, Mingming; Li, Chuanrong (Frontiers in Plant Science, 2022)
To explore the adaptation of the fine root morphology and chemical characteristics of Tamarix chinensis to water–salt heterogeneity in the groundwater–soil system of a coastal wetland zone, T. chinensis forests at different groundwater levels (high: GW1 0.54 m and GW2 0.83 m; medium: GW3 1.18 m; low: GW4 1.62 m and GW5 2.04 m) in the coastal wetland of the Yellow River Delta were researched, and the fine roots of T. chinensis standard trees were excavated. The fine roots were classified by the Pregitzer method, and the morphology, nutrients, and nonstructural carbohydrate characteristics of each order were determined. The results showed that the groundwater level had a significant indigenous effect on the soil water and salt conditions and affected the fine roots of T. chinensis. At high groundwater levels, the specific root length and specific surface area of fine roots were small, the root tissue density was high, the fine root growth rate was slow, the nutrient use efficiency was higher than at low groundwater levels, and the absorption of water increased with increasing specific surface area. With decreasing groundwater level, the N content and C/N ratio of fine roots first decreased and then increased, and the soluble sugar, starch, and nonstructural carbohydrate content of fine roots first increased and then decreased. At high and low groundwater levels, the metabolism of fine roots of T. chinensis was enhanced, and their adaptability to high salt content and low water content soil environments improved. The first- and second-order fine roots of T. chinensis were mainly responsible for water and nutrient absorption, while the higher-order (from the third to fifth orders) fine roots were primarily responsible for the transportation and storage of carbohydrates. The fine root morphology, nutrients, nonstructural carbohydrate characteristics, and other aspects of the water and salt environment heterogeneity cooperated in a synergistic response and trade-off adjustment.